Determination of drying characteristics and effective diffusivity for sugar cubes - Akosman, C (Wiley-V C H Verlag Gmbh, 2004)
In this study, the drying characteristics of sugar cubes have been investigated. Drying experiments with sugar cubes were conducted in a laboratory-type tray dryer at temperatures ranging from 45 to 95 degreesC and different air velocities (0.43, 0.56, and 0.7 m/s). Drying rates increased with the increase in temperature and air velocity. At high temperatures, the moisture content of the solid reached equilibrium moisture value in short time periods. Experimental data were analyzed by using the analytical solution of the unsteady-state diffusion equation to determine the effective diffusivity in sugar cubes.